Marcus Aureliu’s pedagogical figure through Herodian’s vision - Esteller, Lorena (Romanitas - Revista de Estudos Grecolatinos, 2016)
The main task of this paper is to present emperor Marcus Aureliu’s pedagogical figure by the hand of Herodian in History of the Roman Empire. A double task was followed here. Firstly, to enlighten Herodian’s unique and complete work, dated from the 3rd century, and to show how he conceives the emperors of his time. Finally, to show Marcus Aureliu’s pedagogical relevance by linking his figure as good emperor together with the philosophical one.